2011
DOI: 10.1097/jcp.0b013e31822c0a68
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Functional Improvement in Employed Depressed Patients

Abstract: Desvenlafaxine 50 mg/d was efficacious for treating MDD in gainfully employed adults. Between-group differences on the SDS narrowly missed statistical significance in the ITT population alone, but the totality of data suggests functional improvements with active treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 33 publications
(22 reference statements)
0
19
0
Order By: Relevance
“…The SDS is a validated measure of functional impairment that has demonstrated sensitivity to impairment and the effects of treatment across a wide range of disorders, including MDD (Sheehan & Sheehan, 2008). The SDS has been used to assess functional improvement in association with improvements in depressive symptoms for duloxetine (Mancini et al., 2012; Oakes et al., 2012; Sheehan et al., 2011; Wise et al., 2008), desvenlafaxine (Dunlop et al., 2011; Guico‐Pabia et al., 2012; Soares et al., 2009), paroxetine (Wise et al., 2008), bupropion (Hewett et al., 2010; Soczynska et al., 2014), escitalopram (Romera et al., 2012; Soczynska et al., 2014), venlafaxine (Fann et al., 2015; Hewett et al., 2010), levomilnacipran (Asnis et al., 2013; Sambunaris, Bose, et al., 2014), and agomelatine (Montgomery, Nielsen, et al., 2014; Zajecka et al., 2010) with results that have been variable with respect to clinical significance; however, many of these antidepressants showed significant differences versus placebo in the change from baseline versus placebo in the SDS total score when patients were stratified by baseline depressive symptom severity. A recent pooled analysis showed that treatment with duloxetine ( n  = 1,029) and SSRIs ( n  = 835) resulted in significantly greater improvements in the SDS total score (∆ −1.9, p  <   .001; ∆ −1.7, p  <   .01, respectively) compared to placebo ( n  = 329).…”
Section: Discussionmentioning
confidence: 99%
“…The SDS is a validated measure of functional impairment that has demonstrated sensitivity to impairment and the effects of treatment across a wide range of disorders, including MDD (Sheehan & Sheehan, 2008). The SDS has been used to assess functional improvement in association with improvements in depressive symptoms for duloxetine (Mancini et al., 2012; Oakes et al., 2012; Sheehan et al., 2011; Wise et al., 2008), desvenlafaxine (Dunlop et al., 2011; Guico‐Pabia et al., 2012; Soares et al., 2009), paroxetine (Wise et al., 2008), bupropion (Hewett et al., 2010; Soczynska et al., 2014), escitalopram (Romera et al., 2012; Soczynska et al., 2014), venlafaxine (Fann et al., 2015; Hewett et al., 2010), levomilnacipran (Asnis et al., 2013; Sambunaris, Bose, et al., 2014), and agomelatine (Montgomery, Nielsen, et al., 2014; Zajecka et al., 2010) with results that have been variable with respect to clinical significance; however, many of these antidepressants showed significant differences versus placebo in the change from baseline versus placebo in the SDS total score when patients were stratified by baseline depressive symptom severity. A recent pooled analysis showed that treatment with duloxetine ( n  = 1,029) and SSRIs ( n  = 835) resulted in significantly greater improvements in the SDS total score (∆ −1.9, p  <   .001; ∆ −1.7, p  <   .01, respectively) compared to placebo ( n  = 329).…”
Section: Discussionmentioning
confidence: 99%
“…4–7 However, fewer than 40% of patients achieve remission with initial treatment, 8,9 and choosing the “wrong” initial treatment has significant individual and societal costs due to continued distress, risk of suicide, loss of productivity, and wasted resources associated with 2 to 3 months of an ineffective treatment. 10,11 Given the public health consequences of inadequately treated depression, a clinical or biological marker to guide initial treatment selection for MDD could have major health and economic impact. 12 …”
mentioning
confidence: 99%
“…Around 160 studies did not provide adequate side‐effect data on hyperhidrosis for contribution to meta‐analysis outcomes. Our meta‐analysis involved data from 76 trials involving 28544 subjects (Allgulander et al., ; Baldwin, Bobes, Stein, Scharwachter, & Faure, ; Baldwin, Loft, & Dragheim, ; Bose et al., ; Boulenger, Loft, & Olsen, ; Bradwejn et al., ; C. Allgulander, , ; Chouinard, ; Claghorn et al., ; Coric et al., ; D. S. Baldwin, ; Detke et al., ; Dominguez, Goldstein, Jacobson, & Steinbook, ; Dunbar et al., ; Dunlop et al., ; Edwards & Goldie, ; Fabre et al., ; Fabre, Birkhimer, Zaborny, Wong, & Kapik, ; Feighner et al., ; Feighner, Boyer, Meredith, & Hendrickson, ; Gaynor et al., ; Gaynor et al., ; Gelenberg et al., ; Golden, Nemeroff, McSorley, Pitts, & Dube, ; Henigsberg, Mahableshwarkar, Jacobsen, Chen, & Thase, ; Hewett et al., ; Hewett et al., ; Hewett et al., ; Kasper et al., ; Katona, Hansen, & Olsen, ; Kiev & Feiger, ; Koponen et al., ; Lader et al., ; Lecrubier, Bakker, Dunbar, & Judge, ; Lenox‐Smith & Reynolds, ; Lepola et al., ; Lepola, Bergtholdt, St. Lambert, Davy, & Ruggiero, ; Liebowitz et al., ; Liebowitz et al., ; Liebowitz et al., ; Liebowitz, Asnis, Mangano, & Tzanis, ; Liebowitz, Gelenberg, & Munjack, ; Liebowitz, Mangano, Bradwejn, & Asnis, ; Liebowitz, Tourian, Hwang, & Mele, ; Mahableshwarkar, Jacobsen, & Chen, ; Mahableshwarkar, Jacobsen, Chen, & Simon, ; Mahableshwarkar, Jacobsen, Serenko, & Chen, ; Mendels et al., ; Montgomery et al., ; Nicolini et al., ; Nierenberg et al., ; Nimatoudis et al., ; Pollack et al., ; Polla...…”
Section: Resultsmentioning
confidence: 99%